SIFAT PEMESINAN 36 JENIS KAYU DARI DAERAH IRIAN JAYA - Osly Rachman; Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1987)
This article presents test results of the machining properties  of 36 wood species from  Manokwari,  lrian Jaya.  The test method used was the modified  ASTM D-1666 described in Forest Products  Research Institute Report No.160 (1982). In most of the species 25 or more samples  were available for test. All test material was dried to equilibrium Moisture content condition (15 to 18% moisture  content). The machining properties that were investigated were planing, shaping, boring,   mortising, turning and sanding.Some of  the species tested are consistenly better than average in most respects. The species have good machining properties are sehiega.koesigoro, seyam, matoa, kerbai and petian.   Whereas some species, such as fofo, sehiye, wafut, basuoh,  serakka  and  bimiek  are consistently poorer. The others species are good  in some properties  and fair  or poor in others.